2013
DOI: 10.1186/1471-244x-13-229
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the abbreviated version of the Scale to Assess Unawareness in Mental Disorder in schizophrenia

Abstract: BackgroundThe Scale to Assess Unawareness in Mental Disorder (SUMD) is widely used in clinical trials and epidemiological studies but more rarely in clinical practice because of its length (74 items). In clinical practice, it is necessary to provide shorter instruments. The aim of this study was to investigate the validity and reliability of the abbreviated version of the SUMD.MethodsDesign: We used data from four cross-sectional studies conducted in several psychiatric hospitals in France. Inclusion criteria:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 62 publications
1
34
0
1
Order By: Relevance
“…31 Poor insight into their disease process occurs in 30-50% of people with schizophrenia and is related to suboptimal outcomes. [32][33][34] In fact, studies of adherence to AP medication found that poor insight among people with schizophrenia is the best predictor of nonadherence. 32 A quality relationship between the person with schizophrenia and their health-care provider ( Fig.…”
Section: Person-centred Approachmentioning
confidence: 99%
“…31 Poor insight into their disease process occurs in 30-50% of people with schizophrenia and is related to suboptimal outcomes. [32][33][34] In fact, studies of adherence to AP medication found that poor insight among people with schizophrenia is the best predictor of nonadherence. 32 A quality relationship between the person with schizophrenia and their health-care provider ( Fig.…”
Section: Person-centred Approachmentioning
confidence: 99%
“…Furthermore, it is not possible to determine a causal direction for the observed relationship between change in insight and improvement in negative and disorganized symptoms, as it is possible that symptom improvements led to improvements in insight In addition, our measure of insight consisted of a single item on the PANSS, rather than multidimensional measure of insight. Although, the PANSS insight item has been found to be strongly correlated with multidimensional measures of insight 24 , more nuanced measures of insight are preferable.…”
Section: Discussionmentioning
confidence: 99%
“…This version has shown good reliability and validity. It comprises three items for general awareness, three items for positive and three items for negative symptoms 8 . Self-stigma was assessed with the Internalized Stigma of Mental Illness (ISMI).…”
Section: Methodsmentioning
confidence: 99%